Impact of Human Resource Management Practices on Employee Retention in Education Sector of Hazara Division Pakistan - Qasim, Awais; Saleem , Farida; yadewani , Dorris (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose - Retention of employees has been shown to be of great importance for expansion and achievement of business goals, especially when it comes to gaining competitive advantage over other companies in the period of increasing globalization. Nowadays, changes in technology, global economy, trade agreements, etc., directly affect employee-employer relations, resulting in high employee turnover, thus affecting employee retention in a company. The objective of the study was to determine the perceived relationship between employee retention and practices in the education sector of Hazara Division in Pakistan. Methodology/approach – A descriptive survey design was adopted for the study as it ensures a complete description of the situation, thus ensuring minimal bias in data collection and reducing errors in the interpretation of the data collected. Primary data was collected for the study using a structured questionnaire. The data collected was analyzed using descriptive Statistics comprising of frequencies, distribution percentages, mean and standard deviation. The study originates there are significant positive relation employee retention with Recruitment and selection, performance management and training and development. Findings – The basic conclusion of the current study is the employees of the education sector should focus or adopt recruitment & selection process to improve their organizational performance. By acting performance management, they adopt motivate to their followers and also bring new ideas and strategies to improve the organizational setting or performance. Similarly, the education employees adopt the training and development for development of employees’ skills. It is also recommended the leaders of education sides must involve their employee in the process of decision making it also gives direction to improve their performance.